PENERAPAN MODEL DISCOVERY TERARAH BERBASIS LINGKUNGAN UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA MATERI STRUKTUR DAN FUNGSITUMBUHAN SISWA KELAS IV SD ISLAM NU PUNGKURAN KECAMATAN SEMARANG TENGAH KOTA SEMARANG TAHUN PELAJARAN 2016/ 2017 - Nur Aina Dwi Wulandari; Iswahyudi Joko S; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This improvement is motivated by the problem of low learning outcomes and critical thinking skills of IPA on the material Structure and Function of PlantSection. Most students' critical thinking skills have not yet been seen and scoredunder the KKM. Therefore, teachers apply environmentally directed discoverylearning model in order to create a fun learning atmosphere. The purpose of thisimprovement is to know the improvement of learning outcomes and criticalthinking skills in science learning materials Structure and Function Part Plantsof fourth graders Semester 1 Islamic elementary school NU Pungkuran DistrictSemarang Central Semarang City Lesson 2016/2017.The implementation oflearning improvement consists of 2 cycles. Cycle I dated October 4, 2016 andCycle II dated October 11, 2016. The results obtained are the increase in thepercentage completeness of student learning outcomes cycle I reached 67%, andcycle II reached 92%. While the achievement of critical thinking skills in the firstcycle reached 58.3% with predicate enough and cycle II increased to 83.3% witha range of intervals from 2.40 to 2.79 predicate enough. The conclusion is thatthe application of environmentally directed discovery learning model canimprove learning outcomes and critical thinking skills of students in sciencelearning materials Structure and Function of Class Section IV Semester 1 SDIslam NU Pungkuran District Semarang Tengah Semarang City Lesson2016/2017.Keywords: discovery, learning outcomes, critical thinking skills.